Feeding oil versus calcium salt of n-6 and n-3 fatty acid on feed intake, digestibility, enteric methane emission and blood metabolic profile in cattle (Bangladesh Journal of Livestock Research, 2020)
A study was conducted to know effects of dietary oils and calcium salts (Ca-salts) of n-6 and n-3 fatty acid (FA) on feed intake, digestibility, enteric methane and blood metabolic profiles in bull. Four rumen cannulated bulls were used in 4x4 Latin Square Designs and supplied with Napier silage and concentrate mixture. Four dietary treatments were sunflower oil (SFO; n-6), linseed oil (LSO;n-3), Ca-salt of SFO (Ca-SFO; n-6) and Ca-salt of LSO (Ca-LSO; n-3). Oils and salts were mixed with concentrate part of the ration at 3% (w/w). Data were analyzed for ANOVA in 2x2 Factorial arrangements. It was found that, intake of DM (p